Qualitative and Quantitative Traits of Thin Tail Ewes in Bojonegoro East Java, Indonesia - Irida Novianti; Mashudi; M. Halim Natsir; Poespitasari H. Ndaru; Veronica Margareta Ani Nurgiartiningsih; Sambas Widiyanto (Jurnal Penelitian Pendidikan IPA, 2026)
Thin-tail sheep is a local genetic resource widely raised by farmers and requires conservation through appropriate breeding programs. This study aimed to characterize quantitative and qualitative traits of thin-tail ewes reared at PT Juara Farm, Bojonegoro. A total of 66 ewes aged 1–4 years were observed, with quantitative traits including body weight, body length, body height, and chest girth, and qualitative traits focusing on tail shape. Data were analyzed descriptively. The results showed that all body measurements increased with age, with body weight ranging from 23.08 ± 3.83 kg in 1 – <2 years to 29.25 ± 3.79 kg in 3–4 years. Similar increasing trends were observed for body length, body height, and chest girth. Three tail shapes were identified: triangular (48.48%), straight (42.42%), and sigmoid (9.10%). The coefficient of variation indicated that body weight had higher variability compared to other traits. In conclusion, thin-tail ewes exhibit age-related increases in body size with moderate phenotypic variability, providing baseline information for breeding and conservation programs.